Agent-assisted VSSe ternary alloy single crystals as an efficient stable electrocatalyst for the hydrogen evolution reaction. Issue 26 (12th June 2019) - Hu, Peng; Long, Guankui; Chaturvedi, Apoorva; Wang, Shancheng; Tan, Kejie; He, Yongming; Zheng, Lu; Liu, Guowei; Ke, Yujie; Zhou, Yang; Jiang, Hui; Liu, Zheng; et al.
Abstract : New ternary VSSe alloy single crystals were synthesized and used as an excellent HER electrocatalyst due to the pure conductive phase and abundant active sites. Abstract : Transition metal dichalcogenides (TMDs) show promising electrical and electronic properties and potential catalytic applications in the hydrogen evolution reaction (HER). However, most TMDs suffered from low conductivity and scarcity of active edge sites. Herein, new ternary vanadium-based TMD, VSSe alloy single crystals were synthesized for the first time by agent-assisted chemical vapor transport and used as an excellent HER electrocatalyst due to the pure conductive phase and abundant active sites induced by ternary structures. Different transport agents were employed to tune the interlayer spacing, and it was found that the expansion of the (001) interlayer spacing and the co-existence of V 3+ could introduce more S or Se vacancies. The exfoliated VSSe sample exhibits a lower overpotential of −180 mV at a current density of 10 mA cm −2, a Tafel slope of 87 mV dec −1, and better durability, which are comparable to or better than those of most previously reported ternary TMD systems. Consistent with the theoretical calculation results, more defects controlled by the transport agent of VCl3 give an enhanced conductivity and a lower H* adsorption energy, and thereby higher HER performance. By simply varying the transport agents, high-conductivity, high-purity, and high-performance TMDs can be fabricated in one step without the conventional post-treatment.